2018
DOI: 10.1111/ele.13190
|View full text |Cite
|
Sign up to set email alerts
|

Environmental gradients and the evolution of tri‐trophic interactions

Abstract: Long‐standing theory predicts herbivores and predators should drive selection for increased plant defences, such as the specific production of volatile organic compounds for attracting predators near the site of damage. Along elevation gradients, a general pattern is that herbivores and predators are abundant at low elevation and progressively diminish at higher elevations. To determine whether plant adaptation along such a gradient influences top‐down control of herbivores, we manipulated soil predatory nemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
(71 reference statements)
1
23
0
1
Order By: Relevance
“…VOCs for attracting predators) than in direct resistance. In a previous study, we showed that F. rubra ecotypes attracting more EPNs in olfactometers were those also surviving the best in the field, under herbivory (Kergunteuil, Röder, et al, ). Investment in attractive VOC blend production seems thus an efficient strategy for warding off herbivores, even when direct resistance is impaired.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…VOCs for attracting predators) than in direct resistance. In a previous study, we showed that F. rubra ecotypes attracting more EPNs in olfactometers were those also surviving the best in the field, under herbivory (Kergunteuil, Röder, et al, ). Investment in attractive VOC blend production seems thus an efficient strategy for warding off herbivores, even when direct resistance is impaired.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, Dobzhansky () postulated that the intensity of biotic interactions increases at the warmer and more stable tropical latitudes and this in turn should select for higher values of traits mediating these interactions (Schemske, Mittelbach, Cornell, Sobel, & Roy, ). Accordingly, tropical (Bolser & Hay, ; Coley & Aide, ; Coley & Barone, ; Moles, Wallis, et al, ; Rasmann & Agrawal, ) and low‐elevation (Dostálek et al, ; Kergunteuil, Röder, & Rasmann, ; Pellissier, Roger, Bilat, & Rasmann, ; Scheidel & Bruelheide, ; Zehnder et al, ) plants should be selected for producing higher values of defence‐related traits. Nonetheless, exceptions from this pattern exist (Moles, Bonser, Poore, Wallis, & Foley, ; Moles, Wallis, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the sources of variation will thus require combining environmental manipulations with reciprocal transplant experiments, possibly complemented by genomic approaches to determine the genetic bases for trait variation, patterns of gene expression, as well as manipulations of relevant traits. Third, studies of environmental gradients must move beyond characterising individual food chains (reviewed by Moreira et al ; Defossez et al ; Kergunteuil et al ) to explicitly characterise and compare multiple, co‐occurring tri‐trophic food chains. This approach is analogous to other trait‐based approaches ( sensu McGill et al ), but with a simultaneous focus on plants, herbivores, and natural enemies as well as traits relevant to TTIs (e.g.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%